ENHANCING 5TH GRADE READING SKILL IN DESCRIPTIVE TEXT AT YP HKBP 1 PEMATANGSIANTAR THROUGH GENRE-BASED APPROACH - Duma Simanjuntak; Netania Saragih; Frans Panjaitan; Herman (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2025)
This community service aimed to enhance fifth-grade students' reading comprehension in descriptive texts using the Genre-Based Approach (GBA). The issue addressed was students' limited reading proficiency in recognizing text structure, vocabulary, and detailed information in descriptive texts. The program applied a systematic instructional model consisting of preparation, implementation, and evaluation phases. Nineteen students from SD YP HKBP 1 Pematangsiantar participated. Data were collected through pre-tests, post-tests, classroom observations, and interviews. This study confirmed the effectiveness of GBA as a sustainable method for early literacy development in elementary education.